THE DESCRIPTION OF THE NEED FOR HOME CARE FOR POSTPARTUM WOMEN WITH CESAREAN SECTION DELIVERY DURING THE COVID-19 PANDEMIC - Ni Ketut Ayu Sugiartini; Putu Krisa Lila Samhita; Andini Mbati Anahida (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2022)
Background: Childbirth requires a physiological process, but pathological conditions or complications can arise from pregnancy to delivery such as Cesarean Section. The purpose of this study was to identify the description of home care for postpartum mothers with Cesarean Section during the Covid-19 Pandemic.Methods: The design of this research is descriptive quantitative, was carried out at Udayana Hospital Denpasar with 30 respondents post Cesarean Section. The sampling technique is purposive sampling. Data was collected by questionnaire and data analysis was carried out by descriptive statisticsResult: The results showed that half 50% of respondents needed vital sign monitoring during the postpartum period post Cesarean Section, most of the 60% respondents needed physical examination monitoring during the postpartum period post Cesarean Section, most of the 66.67% respondents needed psychological care during the postpartum period post Cesarean Section, almost entirely 86.67% of respondents require treatment for mobilization needs during the postpartum period post Cesarean Section, most 53.3% of respondents require treatment for family planning services during the postpartum period post Cesarean Section, almost 90% of respondents require breast care during the postpartum period post Cesarean Section, almost a total of 83.33% of respondents require wound care during the postpartum period post Cesarean Section.Conclusion: Based on the results of the study it was found that the postpartum women who had Cesarean Section, needed a home care during the pandemic.